Fundamental Studies of Rapidly Fabricated On-Chip Passive Micromixer for Modular Microfluidics - Wenpeng Guo; Li Tang; Biqiang Zhou; Yingsing Fung (Micromachines, 2021)
Micromixers play an important role in many modular microfluidics. Complex on-chip mixing units and smooth channel surfaces ablated by lasers on polymers are well-known problems for microfluidic chip fabricating techniques. However, little is known about the ablation of rugged surfaces on polymer chips for mixing uses. This paper provides the first report of an on-chip compact micromixer simply, easily and quickly fabricated using laser-ablated irregular microspheric surfaces on a polymethyl methacrylate (PMMA) microfluidic chip for continuous mixing uses in modular microfluidics. The straight line channel geometry is designed for sequential mixing of nanoliter fluids in about 1 s. The results verify that up to about 90% of fluids can be mixed in a channel only 500 µm long, 200 µm wide and 150 µm deep using the developed micromixer fabricating method under optimized conditions. The computational flow dynamics simulation and experimental result agree well with each other.